2002
DOI: 10.1046/j.1464-410x.2002.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of stress urinary incontinence after radical prostatectomy

Abstract: SummaryUp to 30% of patients complain about urine leakage after radical prostatectomy, but persistent stress incontinence ( beyond 1 year) affects <5% of them. This complication is mainly caused by sphincter dysfunction. Some preventive measures have been described to decrease the risk of incontinence after radical prostatectomy, but with conflicting results. The effectiveness of preoperative and early postoperative physiotherapy is controversial. Moreover, while meticulous apical dissection of the prostate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 51 publications
(81 reference statements)
0
68
0
4
Order By: Relevance
“…The majority of the authors use the number of pads needed per day, other study groups define urinary continence according to the situation when patients lose urine (laughing, coughing, etc). 2,12,13 We defined patients as fully continent, if no pads were needed. That means that patients who also, used a pad for feeling secure but did not lose any urine at all were regarded as stressincontinent I.1…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the authors use the number of pads needed per day, other study groups define urinary continence according to the situation when patients lose urine (laughing, coughing, etc). 2,12,13 We defined patients as fully continent, if no pads were needed. That means that patients who also, used a pad for feeling secure but did not lose any urine at all were regarded as stressincontinent I.1…”
Section: Discussionmentioning
confidence: 99%
“…In 3 randomized controlled trials, PFMT after RP was evaluated using the IIQ-7 to assess patient QQL (2,9,15). In none of the studies, the QOL improved in the treatment group, even in one that revealed better continence in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…UI develops in the majority of patients during the early postoperative days. Peyromaure et al (2) emphasized that early UI affects 30% to 50% of patients from 3 weeks to 6 months after RP. Rates vary widely due to survey methods, the definition of incontinence and surgical technique.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent incontinence negatively affects the post-operative quality of life and is of more concern than erectile dysfunction, especially in older patients [2]. Peyromaure et al reported that early UI affects 30% to 50% of patients from 3 weeks to 6 months after RP [3]. Post prostatectomy incontinence (PPI) is demonstrated widely, ranging from slight leakage with heavy lifting to continuous or gravitational leakage requiring multiple pads or even a penile clamp [4].…”
Section: Introductionmentioning
confidence: 99%